PENINGKATAN SIKAP PERCAYA DIRIDAN HASIL BELAJAR MAPEL IPS MELALUI MODELPEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) - Setiawati, Esti; Surono, Ari (Program Magister Pendidikan IPS UPY, 2024)
This study aims to improve student learning outcomes in Mupel Social Studies learning through the Student Facilitator and Axpaining (SFE) Learning Model in Class V of Brondong State Elementary School, Bruno District, Purworejo Regency, Academic Year 2021/2022. This research is a Classroom Action Research (PTK) which was conducted in 2 cycles. Based on the results of this study it can be concluded that the application of the Student Facilitator and Explaining (SFE) learning model can increase students' self-confidence as evidenced from the pre-cycle with a good category of 26.19%, an increase in cycle I to 46.15%, and a cycle II increased to 65.38%, as well as the learning outcomes of students in social studies content in Class V as evidenced by the increase in the average student completeness of 26.92% in the pre-cycle, up to 57.69% in cycle I and increased again in cycle II of 88.46%. Therefore, the student facilitator and explaining learning model can be applied as an alternative in increasing students' self-confidence and learning outcomes.